Teaching Descriptive Paragraph Writing by Using Ã¢â‚¬Å“Semantic Mapping StrategyÃ¢â‚¬Â to The Tenth Grade Students of MA Nurul Huda SukarajaÃ¢â‚¬Â. - Zulaikah, Zulaikah; Afas, Muhammad Zainudin (IAI Darussalam, 2016)
The purpose of this study was to determine whether there was a significant difference between students who were taught to write descriptive paragraphs using